THE EFFECT OF LIQUIDITY, PROFITABILITY AND CAPITAL INTENSITY ON TAX AGGRESSIVENESS WITH COMPANY SIZE AS A MODERATING VARIABLE - Azzahra Maharani; Feliana Wulansari; Syiva Salwa Yumna; Mohamad Zulman Hakim; Dewi Rachmania; Sigit Budi Santoso (International Journal of Accounting, Management, Economics and Social Sciences (IJAMESC), 2025)
This study analyzes the effect of liquidity, profitability, and capital intensity on tax aggressiveness with company size as a moderating variable in transportation and logistics companies listed on the IDX for the period 2019-2023. Using secondary data from 60 companies and panel data regression methods. The results show that profitability and capital intensity have no effect on tax aggressiveness, while liquidity have a significant effect. Company size moderates the relationship liquidity on tax aggressiveness, but does not moderate between profitability and capital intensity.